Mogok Kerja Tenaga Medis: Problematika pada UU Ketenagakerjaan dan Pilihan Model Pengaturannya - Agung, Rama (Jurnal Hukum & Pembangunan, 2025)
The issue of healthcare workers' strikes remains complex in terms of regulatory frameworks. On one hand, there is a conflict of interest between public interest in access to healthcare services and, on the other, the Labor Law, which regards the right to strike as a fundamental right of workers, integral to collective bargaining. This paper examines the challenges in regulating healthcare workers' strikes by analyzing Article 139 of the Labor Law and exploring regulatory models that support the provision of high-quality healthcare services. The findings highlight several key points. First, Article 139 of the Labor Law does not yet provide a proportional approach to balancing the right to strike with the right to healthcare. This is due to rigid interpretations of the term "public interest," ambiguities in norms, a lack of alignment with the core essence of striking, and weakened access to striking. Empirical studies also reveal that strict conditions often make it challenging for strikes to be legally recognized, thus limiting worker protection. Second, two regulatory models are proposed for managing healthcare workers' strikes: a prohibition model with an arbitration mechanism and a controlled strike model implementing a Minimum Service Level (MSL). The author argues that the MSL model could achieve a reasonable balance between workers' ability to strike and the obligation of the government and employers to ensure proportionally accessible, quality healthcare services.